A STUDY ON FAMILY ENVIRONMENT AND ITS EFFECT ON ACADEMIC ACHIEVEMENT IN SCIENCE AMONG SECONDARY SCHOOL STUDENTS - Pappattu, Jasar; Vanitha, J. (International Journal of Research -GRANTHAALAYAH, 2017)
Family environment seems to impact academic performance. Families in common and parents in specific, have often been considered to be the most significant support system obtainable to the child. The toughest factor in molding a child’s character or behavior is the relationship with their parents. Students who have struggled educationally in most circumstances are at higher risk of school avoidance, and eventually dropping out, than those who are effective. For the struggling students, however, school is often a place that only helps to strengthen the low self-esteem. The student attempts to evade these state of mind of failure by staying home. The main motive is to study on family environment and its effect on academic achievement in science. This research is under taken with a view to examining the family environment and its effect on academic achievement in science among secondary school students with a sample size 300 from 8 schools of Palakkad district. Normative Survey method is used. The study concluded that there doesn’t exist any relationship between family environment factors and achievement in science skills among secondary school students.